GLOBAL AND GLOCAL IN MODERN COMMUNICATION AS A FACTOR OF SOCIOCULTURAL TRANSFORMATIONS - Kleshnia, Hanna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. Globalization discourse testifies to a double impact on human existence at the individual and societal levels, transforming the multicultural space, and homogenizing it. Understanding the relationship between global and glocal processes in scientific discourse is present mainly in sociology, politics, and economics. The abovementioned actualizes the need to study the glocal and the global in the activity-communication paradigm, reproducing the substantial foundations of human existence. The aim is the cultural-philosophical understanding of the phenomenon of linguistic discourse of globalization and glocalization in the scientific communication space of postmodernity. Research methods. A sociocultural methodological approach and a complex of methods of scientific knowledge: systems analysis, comparison, and critical analysis were used to achieve the defined goal. A systems approach was used to examine the theoretical, methodological, and source base of the study. Research results. The study of communication processes acquires special relevance in the era of the information society when the communication essence of social realities and the role of communication in the globalized world are being reviewed. A key feature of globalization is the ability of regional production structures to capitalize on the localized effects of agglomeration, stimulating the emergence and long-term consolidation of specific conditions, assets, and opportunities, based on which transnational capital is formed. One of the reasons for the popularity of the theory of glocalization is its sharp contrast with the theory of modernization, which predicted the inevitability of all civilizations following the stages of progress through which Western civilization had passed. The idea of glocalization denies the idea that the whole world will inevitably follow the path of liberalization, the development of capitalist relations, will be more oriented towards consumption, etc. Discussion. Conceptual approaches make it possible to capture the main views on interaction in the space of the global-local binary. It is still quite early to talk about the completion of the ontological and theoretical understanding of glocalization. Researchers have not reached a final agreement on the demarcation of the ontological fields of terms in the chain of "global" - "glocal" - "local". However, the biggest problem lies in the ambiguous interpretation of the very concept of global. Conclusions. The analysis conducted on scientific discourse reveals an ambiguity in the terminological-conceptual vocabulary. While some scientists view globalization and localization as interconnected and mutually reinforcing processes, others see them as two opposing phenomena with significant contradictions between them.